Pyroptosis in spinal cord injury - Yin, Jian; Gong, Ge; Wan, Wenhui; Liu, Xinhui (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) often brings devastating consequences to patients and their families. Pathophysiologically, the primary insult causes irreversible damage to neurons and glial cells and initiates the secondary damage cascade, further leading to inflammation, ischemia and cells death. In SCI, the release of various inflammatory mediators aggravates nerve injury. Pyroptosis is a new pro-inflammatory pattern of regulated cell death (RCD), mainly mediated by caspase-1 or caspase-11/4/5. Gasdermins family are pore-forming proteins known as the executor of pyroptosis and the gasdermin D (GSDMD) is best characterized. Pyroptosis occurs in multiple central nervous system cell types, especially plays a vital role in the development of SCI. We review here the evidence for pyroptosis in SCI, and focus on the pyroptosis of different cells and the crosstalk between them. In addition, we discuss the interaction between pyroptosis and other forms of RCD in SCI. We also summarize the therapeutic strategies for pyroptosis inhibition, so as to provide novel ideas for improving outcomes following SCI.